Improving Dolan Banyumas App: A Design Thinking Approach to Enhance Tourism Services - Indriyani, Ria; Saputro, Rujianto Eko (Journal of Information System and Informatics, 2025)
The Dolan Banyumas application is a digital step to support tourism in Banyumas Regency. However, the results of observations and evaluations conducted show that the design of the user interface (UI) and user experience (UX) of this application is still less than optimal, with incomplete information, confusing navigation, and unattractive application design. This study aims to redesign the application using the Design Thinking approach, which consists of five stages: empathize, define, ideate, prototype, and test stages. Usability was assessed using the System Usability Scale (SUS) with a 10-question Likert scale survey distributed to 30 respondents. Evaluation results using the System Usability Scale (SUS) method showed an increase in the average score from 63 to 81.42, which classifies the app into the “Good” and “Acceptable” categories. Improvements include easier-to-use navigation, more complete tourist information, and the addition of new features such as ticket booking and bus tour maps. The user satisfaction rate increased from 60% to 87%, while efficiency rose by 30%. Based on Net Promoter Score (NPS), the app is categorized as “Promoter.” The Design Thinking approach proved effective in improving the quality of user experience.